Cuddle Care or Love Care Services in Social Media Twitter (X) - Rumenige, Reven; Sigit, Ridzki Rinanto (Jurnal Pustaka Komunikasi, 2023)
Social media is like two sides of the eye that can present aspects of use in positive and negative directions. In this research, the author discusses the other side of using social media X, namely cuddle care / love care services. Generally, these service providers are bridged by an alter ego account because it can cover their identity. This research uses data collection techniques using observation techniques and in-depth interviews. The aim of the research is to find out the motives behind cuddle care / love care service subjects and analyze the goals and reasons for cuddle care / love care service subjects in choosing social media. This research paradigm uses phenomenology to explore individuals subjectively and provide understanding of the phenomena they have experienced. The results of the research found that the source's motive for opening a cuddle care/love care service was because of the feeling of emptiness that had been felt and the feeling of needing a friend to tell stories or complain about without any moral burden and being judged, and the source used social media X because the source had the belief that Social media can be freely use as their needs.